Characterization of Arabidopsis thaliana Hydroxyphenylpyruvate Reductases in the Tyrosine Conversion Pathway - Xu, Jing-Jing; Fang, Xin; Li, Chen-Yi; Zhao, Qing; Martin, Cathie; Chen, Xiao-Ya; Yang, Lei (Frontiers in Plant Science, 2018)
Tyrosine serves as a precursor to several types of plant natural products of medicinal or nutritional interests. Hydroxyphenylpyruvate reductase (HPPR), which catalyzes the reduction of 4-hydroxyphenylpyruvic acid (pHPP) to 4-hydroxyphenyllactic acid (pHPL), has been shown to be the key enzyme in the biosynthesis of rosmarinic acid (RA) from tyrosine and, so far, HPPR activity has been reported only from the RA-accumulating plants. Here, we show that HPPR homologs are widely distributed in land plants. In Arabidopsis thaliana, which does not accumulate RA at detectable level, two homologs (HPPR2 and HPPR3) are functional in reducing pHPP. Phylogenetic analysis placed HPPR2 and HPPR3 in two separate groups within the HPPR clade, and HPPR2 and HPPR3 are distinct from HPR1, a peroxisomal hydroxypyruvate reductase (HPR). In vitro characterization of the recombinant proteins revealed that HPPR2 has both HPR and HPPR activities, whereas HPPR3 has a strong preference for pHPP, and both enzymes are localized in the cytosol. Arabidopsis mutants defective in either HPPR2 or HPPR3 contained lower amounts of pHPL and were impaired in conversion of tyrosine to pHPL. Furthermore, a loss-of-function mutation in tyrosine aminotransferase (TAT) also reduced the pHPL accumulation in plants. Our data demonstrate that in Arabidopsis HPPR2 and HPPR3, together with TAT1, constitute to a probably conserved biosynthetic pathway from tyrosine to pHPL, from which some specialized metabolites, such as RA, can be generated in specific groups of plants. Our finding may have broad implications for the origins of tyrosine-derived specialized metabolites in general.